Study of a Person's Sleep Quality Level in Physiology and Islamic Understanding - Saminan, Saminan; Julisafrida, Linda; Fajri , Nurul (Sean Institute, 2022)
Sleep is an unconscious state that can be awakened by giving sensory stimulation or by other stimuli. This research method refers to the development steps of Borg & Gall, this is only limited to a preliminary study (concept). Sleep functions to give the brain time to repair biochemical or physiological processes that progressively decrease when awake. The regulation of sleep cycles is centered on two specific areas in the brainstem. Sleep quality is a person's ability to maintain sleep to get the appropriate amount of NREM sleep and REM sleep. Sleep quality is a subjective description of one's sleep satisfaction. Adequate and quality sleep can be the foundation of how a person can live a healthy life by following the Prophet's way of sleeping is to tilt the body to the right, while praying to Allah until the eyes feel heavy and through audio, it is like listening to verses from the Al-Quran.